Serpine2 deficiency results in lung lymphocyte accumulation and bronchus‐associated lymphoid tissue formation. Issue 7 (8th April 2016) - Solleti, Siva Kumar; Srisuma, Sorachai; Bhattacharya, Soumyaroop; Rangel‐Moreno, Javier; Bijli, Kaiser M.; Randall, Troy D.; Rahman, Arshad; Mariani, Thomas J.
ABSTRACT: Serine proteinase inhibitor, clade E, member 2 (SERPINE2), is a cell‐ and extracellular matrix‐associated inhibitor of thrombin. Although SERPINE2 is a candidate susceptibility gene for chronic obstructive pulmonary disease, the physiologic role of this protease inhibitor in lung development and homeostasis is unknown. We observed spontaneous monocytic‐cell infiltration in the lungs of Serpine2‐deficient (SE2 ‐/‐ ) mice, beginning at or before the time of lung maturity, which resulted in lesions that resembled bronchus‐associated lymphoid tissue (BALT). The initiation of lymphocyte accumulation in the lungs of SE2 ‐/‐ mice involved the excessive expression of chemokines, cytokines, and adhesion molecules that are essential for BALT induction, organization, and maintenance. BALT‐like lesion formation in the lungs of SE2 ‐/‐ mice was also associated with a significant increase in the activation of thrombin, a recognized target of SE2, and excess stimulation of NF‐κB, a major regulator of chemokine expression and inflammation. Finally, systemic delivery of thrombin rapidly stimulated lung chemokine expression in vivo. These data uncover a novel mechanism whereby loss of serine protease inhibition leads to lung lymphocyte accumulation.—Solleti, S. K., Srisuma, S., Bhattacharya, S., Rangel‐Moreno, J., Bijli, K. M., Randall, T. D., Rahman, A., Mariani, T. J. Serpine2 deficiency results in lung lymphocyte accumulation and bronchus‐associated lymphoid tissue formation. FASEB J. 30, 2615‐2626 (2016). www.fasebj.org